The Effect of Numbered Head Together (NHT ) Cooperative Learning Model and Learning Motivation on Social Studies Learning Outcomes for Grade VII Students of Smp 40 Padang - Fira Zarti; Khairani Khairani (International Journal of Educational Dynamics, 2020)
This study aims to implement the Numbered Head Togerher (NHT) type of cooperative learning model in social studies subjects for grade VII students of SMPN 40 Padang. This research is an experimental research. Research instruments in the form of tests and questionnaires. Data analysis techniques using ANOVA. The results showed (1) student learning outcomes applied to the NHT type cooperative model were higher than student learning outcomes with conventional methods at SMPN 40 Padang. (2) The learning outcomes of students who have high motivation to learn are higher using NHT type cooperative learning models than students who have low motivation with conventional methods. (3) The learning outcomes of students who have lower learning motivation are higher using conventional learning models higher than using NHT learning models. (4) there is an interaction between the use of the Numbered Head Together (NHT) type of cooperative learning model and motivation in influencing student learning outcomes in social studies subjects in class VII SMPN 40 Padang.